(untitled) (Al-Aasar, 2025)
This article explains the role of Dr. Syed Abdullah in Iqbalism. He has also published articles and important essays on Iqbal’s thoughts. He understood the meaning of Iqbalism in the true sense. He has tried to present Iqbal’s philosophy to others in a way that is easy to understand, easy and simple. While he describes poetry and prose, scientific movements, literature, linguistics, political and national ideas, he also presents Iqbal’s philosophy in an excellent way. Here Iqbal’s critique of the West and its significance is highlighted. Iqbal’s writings shed light on the foreign system of society, politics and Islamic teachings. The meaning of Iqbal’s theory of self has been explained. The important components of Iqbal’s philosophy of politics, the perfect man, Iqbal’s ideology of government and caliphate, religion and government, the concept of nationhood, socialism and capital have been highlighted in great detail. By reading this article, one becomes aware of Allama Iqbal’s political, religious, national, democratic, caliphate and moral concepts.